Crossing the hurdle of a low oocyte yield in an in vitro fertilization cycle to obtain mature oocytes - Pratap Kumar; Shubha Rao; Anjali Mundkur; Prashanth Adiga; Rashmi K Ullagaddi; Vidyashree G Poojari (Wolters Kluwer Medknow Publications, 2022)
The complex process of oocyte maturation involves a coordinated set of events to take place so that an adequate number of oocytes can be obtained during an oocyte pickup procedure following controlled ovarian stimulation. A weak link in any of the steps can yield a sparse number of oocytes which can be a setback in the process.